Decreased Immunoglobulin A Concentrations in Feces, Duodenum, and Peripheral Blood Mononuclear Cells of Dogs with Inflammatory Bowel Disease. (6th December 2012) - Maeda, S.; Ohno, K.; Uchida, K.; Nakashima, K.; Fukushima, K.; Tsukamoto, A.; Nakajima, M.; Fujino, Y.; Tsujimoto, H.
<x xml:space="preserve">Abstract</x> Background Although immunoglobulin A (IgA) plays a key role in regulating gut homeostasis, its role in canine inflammatory bowel disease (IBD) is unknown. Hypothesis IgA expression may be altered in dogs with IBD, unlike that observed in healthy dogs and dogs with other gastrointestinal diseases. Animals Thirty‐seven dogs with IBD, 10 dogs with intestinal lymphoma, and 20 healthy dogs. Methods Prospective study. IgA and IgG concentrations in serum, feces, and duodenal samples were measured by ELISA. IgA+ cells in duodenal lamina propria and IgA+ CD21+ peripheral blood mononuclear cells (PBMCs) were examined by immunohistochemistry and flow cytometry, respectively. Duodenal expression of the IgA‐inducing cytokine transforming growth factor β (TGF‐β), B cell activating factor (BAFF), and a proliferation‐inducing ligand (APRIL) was quantified by real‐time RT‐PCR. Results Compared to healthy dogs, dogs with IBD had significantly decreased concentrations of IgA in fecal and duodenal samples. The number of IgA+ CD21+ PBMCs and IgA+ cells in duodenal lamina propria was significantly lower in dogs with IBD than in healthy dogs or dogs with intestinal lymphoma. Duodenal BAFF and APRIL mRNA expression was significantly higher in IBD dogs than in the healthy controls. Duodenal TGF‐β mRNA expression was significantly lower in dogs with IBD than in healthy dogs and dogs with intestinal lymphoma. Conclusions and Clinical Importance IBD dogs have decreased IgA concentrations in feces and duodenum and fewer IgA+ PBMCs, which might contribute to development of chronic enteritis in dogs with IBD.